Gas-phase reaction products and yields of terpinolene with ozone and nitric oxide using a new derivatization agent - Ham, Jason E.; Jackson, Stephen R.; Harrison, Joel C.; Wells, J.R. (Atmospheric environment (1994), 2015)
The new derivatization agent, O-tert-butylhydroxylamine hydrochloride (TBOX) was used to investigate the carbonyl reaction products from terpinolene ozonolysis. With ozone (O3) as the limiting reagent, four carbonyl compounds were detected: methylglyoxal (MG), 4-methylcyclohex-3-en-1-one, (4MCH), 6-oxo-3-(propan-2-ylidene) heptanal (6OPH), and 3,6-dioxoheptanal (36DOH). The tricarbonyl 36DOH has not been previously observed. Using cyclohexane as a hydroxyl radical (OH) scavenger, the yields of 6OPH and 36DOH were reduced indicating the influence secondary OH radicals have on terpinolene ozonolysis products. However, the MG yield increased and the 4MCH yield was unchanged when OH radicals were scavenged suggesting they are only made by the terpinolene + O3 reaction. The detection of 36DOH using TBOX highlights the advantages of a smaller molecular weight derivatization agent for the detection of multi-carbonyl compounds. The product yields from terpinolene ozonolysis experiments conducted in the presence of 20 ppb nitric oxide (NO) remained unchanged except for MG which decreased. However, in experiments where O3 was kept constant at 50 ppb and NO was varied (20, 50, 100 ppb) MG, 6OPH, 36DOH decreased with increasing NO while 4MCH increased with increasing NO. The use of TBOX derivatization if combined with other derivatization agents may address a recurring need to simply and accurately detect multi-functional oxygenated species in air. •Aqueous collection and derivatization of gas-phase terpinolene ozonolysis products.•Multi-functional gas-phase carbonyls detected from terpinolene ozonolysis.•Hydroxyl radical's and nitric oxide's influence on reaction product formation.